STRENGTHEN, PLAN, AND UTILIZE; EXPLORING NOVEL METHOD FOR TEACHING ENGLISH DURING PANDEMIC - Liya Umaroh (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
It has been exactly a year into remote learning. At the beginning of the pandemic, all the things became difficult and hard to do. Shifting from classroom to remote learning was challenging for both teachers and students. “Strengthen, plan, and utilize” were chosen as the best strategies in teaching English specifically during the pandemic. When students and teachers are separated by distance, captivating a strong connection between the two becomes even more important. From thisengagement, the learning process will run on expectation. The purpose of this article are (1) to describe the implementation of novel method (strengthen, plan, and utilize ) during pandemic. (2) to discover students experiences toward this novel method. At the final result of this research found that the novel method was effective because students were enjoy, got benefit, and enhanced their English study